2014
DOI: 10.1371/journal.pone.0106889
|View full text |Cite|
|
Sign up to set email alerts
|

Can We Disrupt the Sensing of Honey Bees by the Bee Parasite Varroa destructor?

Abstract: BackgroundThe ectoparasitic mite, Varroa destructor, is considered to be one of the most significant threats to apiculture around the world. Chemical cues are known to play a significant role in the host-finding behavior of Varroa. The mites distinguish between bees from different task groups, and prefer nurses over foragers. We examined the possibility of disrupting the Varroa – honey bee interaction by targeting the mite's olfactory system. In particular, we examined the effect of volatile compounds, ethers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(71 citation statements)
references
References 30 publications
3
67
0
1
Order By: Relevance
“…The similarity in expression levels of these chemosensory transcripts in the two stages could be explained by the fact that in both stages Varroa requires chemosensing. In the phoretic stage, Varroa needs to differentiates between different bee hosts 11 , while in the reproductive stage, the mite needs to synchronize its reproduction in accordance with the stage of the developing bee pupa 49 . The high expression of these specific transcripts may indicate their importance in chemosensation in both stages, and therefore should be further investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The similarity in expression levels of these chemosensory transcripts in the two stages could be explained by the fact that in both stages Varroa requires chemosensing. In the phoretic stage, Varroa needs to differentiates between different bee hosts 11 , while in the reproductive stage, the mite needs to synchronize its reproduction in accordance with the stage of the developing bee pupa 49 . The high expression of these specific transcripts may indicate their importance in chemosensation in both stages, and therefore should be further investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the knowledge regarding Chelicerata chemosensing is limited to morphological and electrophysiological studies 711 . It is assumed that Chelicera branched from Hexapoda and Myriapoda just after arthropods invaded land (during the late Cambrian period) 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…This is not surprising, as the rear legs are mainly responsible for the mite's locomotion, whereas Varroa forelegs are frequently raised in the air, and can be described as analogous to insect antennae (Eliash et al, 2014;Plettner et al, 2016). This is not surprising, as the rear legs are mainly responsible for the mite's locomotion, whereas Varroa forelegs are frequently raised in the air, and can be described as analogous to insect antennae (Eliash et al, 2014;Plettner et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…and considered to be one of the major causes of honeybee colony losses almost worldwide (Francis et al, 2013;Steinhauer et al, 2018). The main chemosensory organ of the Varroa is situated on the distal dorsal part of each foreleg, containing chemosensory sensilla (Dillier et al, 2006), and has been shown to participate in chemosensing of honeybee volatiles (Eliash et al, 2014). The Varroa life cycle is well synchronized with that of honeybees and can be generally divided into two main phases: a phoretic phase, in which the Varroa parasitizes an adult bee (nurse or forager), and a reproductive phase, in which the Varroa reproduces within the sealed brood cell (Rosenkranz et al, 2010;Evans and Cook, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Again, electrophysiological studies could help to identify the further specificity of the sensilla for further compounds. Such studies have so far only been performed on the front leg of female mites in relation to host finding behavior (Eliash et al, 2014). Male mites spent their whole life cycle within the sealed brood cell without a phoretic phase on the adult bees .…”
Section: Discussionmentioning
confidence: 99%